K. K. Mathew on democracy equality and freedom - Mathew, K. K.; Baxi,Upendra (ed.) (Lucknow, 1978)
The book in your hands is a collection. of addresses and essays by, and excerpts from judicial opinions of, Mr. Justice Mathew. They represent the quintessence of the juristic thinking of a man who has dedicated a lifetime to law and justice. The central themes of the book relate to democracy, equality and freedom in the context of judicial process in India. The essays and opinions marshal a large amount of cognate thinking in the fields of political science. sociology and comparative jurisprudence. A salient theme running throughout the book is the nature of the judicial process and the styles and scope of judicial review apposite to the overarching social and political contexts of a "developing" society like India.
Keywords: Political science